Reducing inequalities in health: a European perspective (London, 2002)
"Socio-economic inequalities in health are present to a greater or lesser extent in all European countries and the available data suggests that the health gap is increasing. Many studies have been conducted to explain inequalities in health and from them much has been learnt about the different contributory factors. However, in practice it seems hard to translate the knowledge of causes into effective interventions and policies. Reducing Inequalities in Health: a European Perspective: * brings together an unrivalled collection of contemporary data on successful policies and interventions * compares differences in approach in several European countries * includes recent evaluation studies * discusses conceptual issues for research * provides examples of good and bad practice in Europe * draws out the policy and research implications for the future With contributions from leading researchers in 14 different European countries, this book provides a comprehensive source of reference for the reader interested in what really works in the field of health promotion and what sort of policies reduce the health gap."